Labor Nurses' Views of Their Influence on Cesarean Birth. Issue 2 (March 2017) - Simpson, Kathleen Rice; Lyndon, Audrey
Abstract: Background: As part of an ongoing study about nurse staffing during labor and birth sponsored by the Association of Women's Health, Obstetric, and Neonatal Nurses (AWHONN), outcomes that may be linked to aspects of labor nursing were considered. The purpose of this study was to see if labor nurses felt they influenced whether a woman has a cesarean birth. These data were used to determine if cesarean birth should be included as an outcome measure in the multistate labor nurse staffing study. Methods: Focus groups were used to explore the role of labor nurses and cesarean birth. Participants were attending the AWHONN national convention in 2015. Two open-ended questions were asked: 1) Do labor nurses influence whether a woman has a cesarean? 2) What specific things do you do as a labor nurse to help a woman avoid a cesarean? Results: Two focus groups were held ( n = 15 and n = 9). Nurses overwhelmingly agreed nursing care can influence mode of birth. They described multiple strategies routinely used to help a woman avoid a cesarean, which were categorized into three main themes: support, advocacy, and interactions with physicians. Support was emotional, informational, and physical. Advocacy involved advocating for women and helping women advocate for themselves. Nurses tried to focus on positive aspects of labor progress when communicating with physicians. Descriptions of interactions with some physicians implied less than optimal teamwork and lack of collaboration. Conclusion: Labor nurses are likely influential in whether some women have a cesarean. They reported consistently taking an active role to help women avoid a cesarean. Promoting vaginal birth as appropriate to the clinical situation was a high priority. Trust, partnership, and respect for roles and responsibilities of each discipline were not evident in some of the clinical situations nurses described. Abstract : Nurses play an important role in helping women in labor avoid avoid a cesarean birth. They offer emotional encouragement, various labor support techniques, and information on what to expect as strategies to promote vaginal birth. They focus on the positve aspects of labor progress when communicating with physicians. The dynamics of the nurse-physician relationship is at times challenging as labor nurses do not always perceive their physician colleage share the same goals and investment for mode of birth.